Mengurai Spesifikasi Metode Tafsirul Qur’an bil Qur’an dalam Buku Kaidah-Kaidah Tafsir Karya Salman Harun - Baeti Rohman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This article tries to explain the method of interpreting the Qur’an bil Qur’an or the method of interpreting the verses of the Qur’an with other verses of the Qur’an. This research uses a qualitative methodology with literature review techniques. In this section, a study is carried out regarding the concepts and theories used based on the literature review. The literature in question is books and articles that discuss methods or styles in interpreting the Al-Qur’an whose primary source is the book Rules of Tafsir by Salman Harun (Professor of Tafsir Science at UIN Jakarta). Through the literature review method, this article finds research results that the form of interpretation of the Al-Qur’an with the Al-Qur’an is essentially divided into two models: First, muttashil interpretation. Second, the interpretation is munfashil. The process of interpreting the Qur’an with the Qur’an is done in at least two ways: First, through history. Second, through notes. The forms of interpretation of the Qur’an with the Qur’an, including: Bayan Al-Mujmal, Takhsisul ‘Amm, Al-Bayan bi Al-Manthuq aw Bi al-Mafhum, Taqyidul Muthlaq.